The Art of Traditional Music Performance Management to Improve Live Performance in Siponjot Village - Purba, Setia Dermawan; Deliana, Frida; Tarigan, Prikuten; Aritonang, Evawany (Talenta Publisher, 2020)
Siponjot village, Humbang Hasundutan is nurtured to be an art village which have already have several art center within the village. Sanggar Seni Silaban Margu (Art Studio) is one of the art studios that is also active in producing wood-based traditional musical instruments. The Silaban Margu periodically holds training for its members to perform art performances. Unfortunately, a performance art that is not well packed will only lose the spotlight while performing art. The main purpose of this community services is to help the performance management by providing knowledge transfer that is beneficial to the art studio in terms of empowering village communities, especially the art studio community, on how to give a punch in a cultural arts show that is associated with the exhibition and marketing of handicraft products that have been produced while creating creative economic transactions.